Off-grid photovoltaic system for illumination - P. Kouřím; M. Libra; V. Poulek (Research in Agricultural Engineering, 2015)
The off-grid photovoltaic (PV) system with batteries and with the LED light source was constructed and tested in in laboratory conditions. The PV system is used for emergency illumination and it is independent of the electric grid. The PV system is suitable for example in agriculture in store, in horse barn or in outdoors place. Description of the construction and testing is presented in this paper as well as results of the tests. The PV system was self-sufficient during the summer and autumn period till the November 3, 2011. Since November the illumination mode was modified. The illumination intensity was lowered, the discharging speed was decreased.